Ketone Bodies Mediate Antiseizure Effects - Jena M. Krueger; Douglas R. Nordli (Pediatric Neurology Briefs)
Investigators from The Barrow Neurological Institute, Creighton University, University of Kentucky and the University of Calgary Faculty of Medicine investigated the effect of ketone bodies and the ketogenic diet on epileptic Kcna1-null mice.